EFFECT OF GIVING ROSE AROMATHERAPY IN DECREASING LABOR PAIN TIME I ACTIVE PHASE - nadiva mauliana saidah; Sri Untari; Laily Himawati (Lppm Unan, 2024)
Background: Labor and birth of a baby is a joyful event, but some women often experience pain during labor. Efforts to reduce discomfort due to labor pain include pharmacological and nonpharmacological therapy, while non-pharmacological one is by administering rose aromatherapy essential oil. Research objectives: This study aims to determine the effect of giving rose aromatherapy to reduce labor pain in the active phase of labor in a comprehensive manner. Methodology: This research uses qualitative descriptive research with a case study. The instrument used uses Varney's 7 step method. Results: Evaluation results of the care provided to Mrs. A with a frequency of 3x within 25-30 minutes, it was found that giving rose aromatherapy was able to reduce labor pain during the first active phase, from severe pain to mild pain. Conclusion: Giving rose aromatherapy has an effect on reducing the scale of labor pain during the first active phase.